UHF RFID Antenna Tag Design and Analysis for Antenna Miniaturization (ELEKTRIKA- Journal of Electrical Engineering, 2019)
This paper proposes four designs of UHF RFID antenna tag with two different radiating element, copper and aluminum, for antenna miniaturization. The main contribution of this work is the unique design that involves a meander line traced in a variety shape of a bowtie antenna. The UHF RFID band is achieved by reshaping a 900 MHz straight line dipole antenna into the form of a bowtie, thus reducing the size of the antenna significantly while maintaining the operating frequency. The effectiveness of the method is tested in multiple steps. First, the antenna tag designs are run through CST software simulations and optimized to achieve desired outcome. Next, the designs are transferred to Silhouette Studio software to be fabricated using a cutting machine, and finally measured using a vector network analyzer. The comparison between the measurement result of the reflection coefficient and the radiation pattern to their respective simulation results shows that they have a good agreement between each other. With further research and improvements, the size of the antenna tag could be further reduced while maintaining or even improving the performance of the antenna tag.